EMOTIONAL INTELLIGENCE’S STRENGTHENS ON AUDIT QUALITY - Ilmawan, Faiz Nuha; Try Setyorini, Christina; Rachmi Fitrijati, Krisnhoe; Rangga Bawono, Icuk (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to analyze emotional intelligence on audit quality with competence as moderation. This study used a quantitative approach. The population in this study is financial auditors in the